GEL THE NEC: a prospective registry evaluating the safety, ease of use, and efficacy of the HydroSoft coil as a finishing device. (30th January 2017) - Brinjikji, Waleed; Amar, Arun P; Delgado Almandoz, Josser E; Diaz, Orlando; Jabbour, Pascal; Hanel, Ricardo; Hui, Ferdinand; Kelly, Michael; Layton, Kennith D; Miller, Jeffrey W; Levy, Elad; Moran, Christopher; et al.
Abstract : Background and purpose: The HydroSoft coil was developed as a finishing coil, ideally to be placed along the aneurysm neck to enhance intracranial aneurysm healing. The GEL THE NEC (Gaining Efficacy Long Term: Hydrosoft, an Emerging, New, Embolic Coil) multicenter registry was developed to assess the safety and efficacy of HydroSoft coils in treating intracranial aneurysms. We report angiographic and clinical results of this prospective registry. Materials and methods: GEL THE NEC was performed at 27 centers in five countries. Patients aged 21–90 years with a ruptured or unruptured aneurysm 3–15 mm in size were eligible for enrollment. The following variables were obtained: demographics/comorbidities, aneurysm geometry, adjunctive devices used, proportion of patients in whom HydroSoft coils were successfully placed, and long-term angiographic outcomes (graded by an independent core laboratory using the Modified Raymond Scale), and procedure-related adverse events. Predictors of good angiographic outcome were studied using χ 2 and t-tests. Results: A total of 599 patients with 599 aneurysms were included in this study. HydroSoft coils were successfully deployed in 577 (96.4%) patients. Procedure-related major morbidity and mortality were 0.5% (3/599) and 1.3% (8/599), respectively. The most common perioperative complications were iatrogenic vasospasm (30/599, 5.0%), thromboemboli (27/599, 4.5%), and aneurysm perforation (16/599, 2.7%). At last angiographic follow-up (mean 9.0±6.3 months), the complete occlusion rate was 63.2% (280/442) and near complete occlusion rate was 25.2% (107/442). The core laboratory read recanalization rate was 10.8% (46/425) and the retreatment rate was 3.4% (20/599). Conclusions: Endovascular treatment of intracranial aneurysms with HydroSoft coils resulted in complete/near complete occlusion rates of 88% and a major complication rate of 1.8%. Trial registration number: NCT01000675 .